Study Planning of Check Dam as Sediment Controller at Sumbersari UB Forest Area - Oktaviariyadi, Nabila; Dermawan, Very; Saputra , Anggara Wiyono Wit (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2023)
The construction of a check dam is proposed as a solution to address multiple environmental challenges in the upstream region of a river. Primarily, the focus is on erosion control, the deceleration of debris flow, and the prevention of sedimentation. The strategic implementation of this plan encompasses a range of methodologies, including topographical measurements, geotechnical testing, hydrological analysis, hydraulics analysis, and the meticulous development of a budget plan for the actual construction of the check dam. Within the study area, sedimentation issues stem from a debris flow characterized by a sediment discharge rate of 0.657 m3/s. This phenomenon coincides with a significant 25-year return period flood discharge of 9.134 m3/s. The proposed check dam emerges as a crucial intervention capable of effectively mitigating the situation for approximately 1 hour and 13 minutes, providing a targeted response to the persisting debris flow. To execute this plan, an estimated budget of IDR 460,859,000 has been projected. This financial allocation encompasses the expenses associated with topographical measurements, geotechnical testing, hydrological and hydraulics analyses, as well as the actual construction of the check dam. Overall, the proposed check dam stands as a multifaceted solution designed to harmonize environmental conservation with sustainable water resource management.